Optimization of Process Parameter on Friction Stir Welding on Aluminium Alloy 6061 Using Taguchi Method - Mohd Amin, Azriszul; Hassan, Faieez Nur Ashraf (Research Progress in Mechanical and Manufacturing Engineering, 2023)
This research looks at the friction stir welding process and how it works on AA6061 plates, a material that is difficult to weld with traditional fusion welding. By using three different tool pin diameters with varying welding parameters, the objectives are to to determine the optimum process parameter of the friction stir welding on aluminium 6061 using taguchi method. The Fiction Stir Welding (FSW) is the alternative method for joining two pieces of metal together without destroying the microstructure of the aluminium alloy 6061. The problem with this method is that there were not many research where it have found the optimum parameter for the Friction Stir Welding process for aluminium alloy 6061. It will take a great amount of material, time and work force to classify the optimum parameter. Tools with pin profile of cylindrical, squared, and triangular which were manufactured by using a normal lathe machine. The welding processes were carried out using a conventional milling machine. The triangular pin was identified as the most effective shape for welding at high speeds. This was attributed to its unique three side design which increases the amount of plastic deformation and stirring of the workpiece to process the workpiece material at an increased rate. The optimum process parameter of the friction stir welding on aluminium 6061 is triangular pin profile, 1583 rpm and 20.09 mm/min.